Humor and National Catharsis in Roberto Cossa’s El saludador - Bulman, Gail A. (Latin American Theatre Review, 2002)
This article examines humor in Roberto Cossa’s El saludador and proposes that, through his unique blend of comic forms, the playwright manipulates audience reaction and provokes catharsis in his spectators. Cossa creates a comic protagonist who is a surrogate for the Argentine nation. Through their identification with the humorous protagonist/nation, spectators can consider their own reaction to the abuses the nation has suffered or self-imposed. Unlike earlier Cossa plays, which may have impeded audience catharsis, the spectator/protagonist/nation identification in El saludador promotes catharsis through audience laughter and allows spectators to purge themselves of economic and political fears in the aftermath of recent events in Argentina’s history. (GB)